Influence of the fetal bovine serum proteins on the growth of human osteoblast cells on graphene - Kalbacova, Marie; Broz, Antonin; Kalbac, Martin (Journal of biomedical materials research. Part A, 2012)
The influence of single-layer graphene produced by chemical vapor deposition on human osteoblast cells under different conditions was studied. Measurements probed the ability of cells to adhere and proliferate on graphene compared with SiO(2)/Si substrates and standard tissue culture plastic when cells were incubated for the first 2 h in the presence or the absence of fetal bovine serum (FBS), thus influencing the initial, direct interaction of cells with the substrate. It was found that after 48 h of human osteoblast incubation on graphene films, there were a comparable number of cells of a similar size irrespective of the presence or the absence of serum proteins. On the other hand, a strong initial influence through the presence of FBS proteins on cell number and cell size was observed in the case of the SiO(2)/Si substrate and control plastic. Thus, our study showed that the initial presence/absence of FBS in the medium does not determine cell fate in the case of a graphene substrate, which is very unusual and different from the behavior of cells on other materials.
Keywords: Cattle; Cell Line; Culture Media; Blood Proteins; Cell Proliferation; kultivační média; osteoblasty; fetální proteiny; skot; grafit; Osteoblasts; buněčná adheze; Graphite; Animals; krevní proteiny; lidé; biokompatibilní materiály; Humans; zvířata; buněčné linie; Fetal Proteins; proliferace buněk; Biocompatible Materials; Cell Adhesion